PEMIKIRAN POLITIK ISLAM IMAM AL-MAWARDI DAN RELEVANSINYA DI INDONESIA - Syam, Syafruddin (Jurnal Ilmiah Al-Hadi, 2018)
As is known that the Islamic world in the past many produces great figures and thinkers whose names and works are still used and used as  references in the face of various situations and problems that occur in the context of Muslim life. Khazanah Islamic intellectuals Abbasid caliphate era ever carved a golden history with the advancement of science and religious thought. One of the leading figures as well as the thinker and founder of the Islamic political scholarship of the Abbasid progress was Al-Mawardi.